Dismantling the dualisms for American Pentecostal women in ministry : a feminist-pneumatological approach - Stephenson, Lisa P. (Global Pentecostal and Charismatic studies ;, 2011)
This book analyzes the historical and theological factors resulting in the present situation among American Pentecostal women in ministry, and proposes a Feminist-Pneumatological anthropology and ecclesiology that address the problematic dualisms that have perpetuated Pentecostal women's ecclesial restrictions.